1977
DOI: 10.1163/002829678x00071
|View full text |Cite
|
Sign up to set email alerts
|

The Morphology of the Head-Muscles of a Generalized Haplochromis Species: H. Elegans Trewavas 1933 (Pisces, Cichlidae)

Abstract: This paper, dealing with the morphology (viz. structure, insertion areas, direction and, to a lesser degree, shape) of the head muscles of Haplochromis elegans, is the second study in a series on the head-morphology of this generalized Haplochromis species from the East-Africa Lakes Edward and George. The shape-descriptions of the skeletal elements, given in the first paper of the series (BAREL et al., 1976), have been used for an accurate definition of the position of the muscles. As well as dissection, graph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1
1

Year Published

1982
1982
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 0 publications
1
45
1
1
Order By: Relevance
“…This can be explained by the opercular region of the gill slit being opened actively (i.e. by force from the dilatator operculi and levator arcus palatini muscles; Anker, 1978) and closed actively (i.e. by force of the adductor opercula and the adductor arcus palatini muscles; Anker, 1978), while the ventral region acts purely as a passive valve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be explained by the opercular region of the gill slit being opened actively (i.e. by force from the dilatator operculi and levator arcus palatini muscles; Anker, 1978) and closed actively (i.e. by force of the adductor opercula and the adductor arcus palatini muscles; Anker, 1978), while the ventral region acts purely as a passive valve.…”
Section: Discussionmentioning
confidence: 99%
“…by force from the dilatator operculi and levator arcus palatini muscles; Anker, 1978) and closed actively (i.e. by force of the adductor opercula and the adductor arcus palatini muscles; Anker, 1978), while the ventral region acts purely as a passive valve. Suction will be created during the opercular abduction phase, resulting in a lower water pressure inside compared with outside the head.…”
Section: Discussionmentioning
confidence: 99%
“…Hoogerhoud (1986b) found that the horn width of the LPE is a good measure to differentiate between animals with a hypertrophied and a reduced LPE. The muscle complex attached to the LPE, the musculus levator externis 4 and the musculus levator posterior (mLE4/LP), were removed, dried and weighed (muscular and skeletal names according to Anker, 1978, andBarel et al, 1976).…”
Section: North Cameroonmentioning
confidence: 99%
“…Several muscles could not be identified from the descriptions given in Winterbottom's work. These were ascribed names with the assistance of work on cichlid pharyngeal anatomy (Anker, 1978;Stiassny, 1981).…”
Section: Pharyngeal Macrostructurementioning
confidence: 99%
“…This muscle, which linked a pharyngobranchial element to the skull base, is probably derived from the transversus dorsalis muscle block, and may be distinguished from the levatores interni by its more median origin on the cranium. Considering this, and its central origin in the pharynx, it is named (using Anker's (1978) terminology) the muscularis cranio-pharyngobranchialis 2 posterior.…”
Section: Edentulous Bonesmentioning
confidence: 99%